Role of spin excitations in the fractional quantum Hall effect at nu=1/3 - Harris, J; Davies, H; Ryan, J; Turberfield, A (1998)
We report resonant inelastic light scattering measurements of collective electronic excitations at filling factor v = 1/3 in a high mobility 2DES at temperatures between 50 mK and 3 K. In a narrow range of temperatures near 1 K the intensity of light scattering from the charge density mode, and the exchange enhancement of the energy of a collective spin excitation, fall rapidly to zero. We deduce that the electron correlation characteristic of the spin-polarized electron liquid at v = 1/3 collapses at 1 K: this collapse is triggered by thermal fluctuations of the electron spin. (C) 1998 Elsevier Science B.V. All rights reserved.